The investment climate of the regions of Kazakhstan: issues of state regulation - Khassenova, K.K.; Shamisheva, N.K.; Issayeva, B.K.; Niyazbekova, Zh.U. (BUKETOV BUSINESS REVIEW, 2020)
Object: The subject of the study is the study of ways to optimize regulatory mechanisms and support from the state, if the investment situation of the regions of Kazakhstan has determined as a purpose the study to show the most effective ways associated with their increase, forming the object of study Methods: statistical analysis, integral potential, methods of integrated risks Findings: The investment climate in the country is the main factor determining the ability of the country to attract foreign investment, as well as the development of small and medium enterprises. From this point of view, the problem of increasing the investment opportunities of the regions and acquiring on their basis the opportunities for the development of small and medium-sized enterprises is one of the most urgent. Therefore, in the article, a comparative analysis of the investment priorities of the regions reflects the relevance of the full implementation of strategically important state programs. Conclusions: The modern mechanisms of state support and regulation of investment attraction processes, indicating the causes of imbalances in the regions of the Republic of Kazakhstan are reflected in this article. Given the diverse industrial and industrial focus of the regions, the need for ongoing support for economic diversification has been taken into account.